2019
DOI: 10.1002/1348-9585.12023
|View full text |Cite
|
Sign up to set email alerts
|

Association between working hours, work engagement, and work productivity in employees: A cross-sectional study of the Japanese Study of Health, Occupation, and Psychosocial Factors Relates Equity

Abstract: Objectives The aims of the study were to investigate the association between working hours, work engagement, and work productivity, and to examine if work engagement moderates the influence of working hours on work productivity. Methods We used cross‐sectional data from the Japanese occupational cohort survey, which involved 2093 employees in a manufacturing industry. Working hours were self‐reported by the study participants. Work productivity was assessed with absolute presenteeism based on the scale of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 24 publications
1
28
0
3
Order By: Relevance
“…There may also be implications for physical and mental health with respect to work–life balance during the COVID‐19 outbreak, as time during stay‐at‐home orders may lack a clear transition between work/school and leisure. Prior review has suggested long working hours may be associated with increased anxiety, depression and cardiovascular disease, although meta‐analytic findings suggest small to negligible effect sizes (Ganster, Rosen, & Fisher, 2018), which are moderated by feelings of work engagement (Okazaki et al, 2019). Importantly, addiction to organizational technologies may have unintended consequences for personal and family life: a study of 241 organizational mobile email users found addiction to mobile email was associated with perceived work overload and technology–family conflict (Turel, Serenko, & Bontis, 2011).…”
Section: Overviewmentioning
confidence: 99%
“…There may also be implications for physical and mental health with respect to work–life balance during the COVID‐19 outbreak, as time during stay‐at‐home orders may lack a clear transition between work/school and leisure. Prior review has suggested long working hours may be associated with increased anxiety, depression and cardiovascular disease, although meta‐analytic findings suggest small to negligible effect sizes (Ganster, Rosen, & Fisher, 2018), which are moderated by feelings of work engagement (Okazaki et al, 2019). Importantly, addiction to organizational technologies may have unintended consequences for personal and family life: a study of 241 organizational mobile email users found addiction to mobile email was associated with perceived work overload and technology–family conflict (Turel, Serenko, & Bontis, 2011).…”
Section: Overviewmentioning
confidence: 99%
“…Work engagement was one of the work-environmental factors examined in association with presenteeism by McGregor et al (2018) [14], who found that work engagement had a strong impact on health conditions but was not significantly associated with presenteeism, after all work environmental factors and health conditions were included in one model. In the aforementioned study by Okazaki et al (2019), work engagement was observed to be positively associated with presenteeism, even when controlling for potential confounders and considering working hours [18]. Eguchi et al (2020) studied the associations between work engagement and presenteeism in a prospective cohort study and reported that work engagement at baseline was significantly associated with absolute presenteeism at follow-up, and this association remained significant after additionally adjusting for work performance at baseline [33].…”
Section: Studies On the Link Between Workers' Positive And Negative Pmentioning
confidence: 99%
“…One study examined the effect of working hours on presenteeism. Okazaki [18]. Nylén et al (2019) studied the association of presenteeism with personal resources-signaling and limitsetting strategies, as well as the demand-control-support (DCS) model.…”
Section: Studies On the Associations Of Various Stress Models And Facmentioning
confidence: 99%
See 1 more Smart Citation
“…Work and working conditions have a significant impact on health [ 3 ]. Stressful situations occur in the worker when these conditions are altered by different factors (work overload, lack of support, work schedules, or lack of family reconciliation) [ 4 , 5 , 6 ], giving rise to a specific type of stress called work stress [ 7 , 8 ]. Work stress is defined as “the reaction that the individual may have to work demands and pressures that do not match his knowledge and skills, and that test his ability to cope with the situation” [ 9 ].…”
Section: Introductionmentioning
confidence: 99%